2022
DOI: 10.15252/emmm.202114740
|View full text |Cite
|
Sign up to set email alerts
|

The Sec61 translocon is a therapeutic vulnerability in multiple myeloma

Abstract: Multiple myeloma (MM) is an incurable malignancy characterized by the uncontrolled expansion of plasma cells in the bone marrow. While proteasome inhibitors like bortezomib efficiently halt MM progression, drug resistance inevitably develop, and novel therapeutic approaches are needed. Here, we used a recently discovered Sec61 inhibitor, mycolactone, to assess the interest of disrupting MM proteostasis via protein translocation blockade. In human MM cell lines, mycolactone caused rapid defects in secretion of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 57 publications
4
22
0
Order By: Relevance
“…However, small Sec61 inhibitors with an enhanced therapeutic index were recently generated, some of which are currently evaluated in Oncology phase 1 trials [13]. Building on our previous study [7], the present work strengthens the notion that blocking Sec61 is a relevant approach for the treatment of refractory or relapsed MM.…”
Section: Crbn Expression [6]supporting
confidence: 76%
See 2 more Smart Citations
“…However, small Sec61 inhibitors with an enhanced therapeutic index were recently generated, some of which are currently evaluated in Oncology phase 1 trials [13]. Building on our previous study [7], the present work strengthens the notion that blocking Sec61 is a relevant approach for the treatment of refractory or relapsed MM.…”
Section: Crbn Expression [6]supporting
confidence: 76%
“…Using mycolactone (Myco) as a model inhibitor, we recently reported that Sec61 (the channel mediating secretory protein import into the ER) is a therapeutic vulnerability in MM [7]. In MM cell lines and patientderived tumors, Myco triggered an atypical, pro-apoptotic ER stress response synergizing with Bz for induction of MM cell death in vitro and in vivo.…”
Section: Crbn Expression [6]mentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting the Sec61 of the translocon, thus disrupting transport of newly secreted or transmembrane proteins into the ER, leads to their degradation by the proteasome, which can eventually lead to cell apoptosis due to continuous proteotoxic stress response. The use of mycolactone, a small molecule that inhibits Sec61, along with PI was found to be effective in inducing apoptosis and synergistic in pre-clinical models of laboratory-derived MM cell lines [ 291 ]. This combination was found to cause enhanced ER stress with activation of pro-apoptotic UPR in MM cells, as reflected on transcript as well as protein levels.…”
Section: Emerging Approaches and Future Directionsmentioning
confidence: 99%
“…The synergy was maintained in bortezomib-resistant MM.1S cell lines, as well as in patient-derived MM cells. This target should be further explored as a potential novel therapeutic approach and drug development [ 291 ].…”
Section: Emerging Approaches and Future Directionsmentioning
confidence: 99%